Permainan Kuda Bisik Untuk Meningkatkan Kemampuan Pembendaharaan Kosakata Anak Usia 5-6 Tahun - Baiq Shofa Ilhami; Baiq Febri Hijriatul Fitri; Sandy Ramdhani (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2019)
This research aims to see results of the development of the Kuda Bisik traditional game to improve the vocabulary of children in group B. The type of development used is to adapt development type of borg gall which has been simplified into 3 main stages namely; needs analysis; product design; and product trials. test subjects using 10 children in limited trials and 22 children from 2 schools with name Ummi Adniyah Pancor Kindergarten and Hamzanwadi Pancor Kindergarten. Data collection techniques used were observation; tests and documentation with instruments used observation sheets; product validation sheet; and test. The analysis technique uses the percentage of test results of learning outcomes with a classical success rate of 75%. The results of his research are in the initial trials of the product in the form of a Kuda Bisik media game well implemented. while the initial field of the 22 samples used from the two schools described the results of observations of the use of Kuda Bisik products to increase vocabulary of children, which began to develop as expected (BSH) by 7 people or with a percentage of 32% and 15 children or 62% is very well developed (BSB), and learning outcomes tests found 8 children or 36% developed as expected, and 14 children or 64% of children developed so well that the Kuda Bisik product was able to improve the vocabulary children age 5-6 years old